Mechanisms of FA-Phagy, a New Form of Selective Autophagy/Organellophagy - Lu, Jiayi; Linares, Bernard; Xu, Zhen; Rui, Yan-Ning (Frontiers in Cell and Developmental Biology, 2021)
Focal adhesions (FAs) are adhesive organelles that attach cells to the extracellular matrix and can mediate various biological functions in response to different environmental cues. Reduced FAs are often associated with enhanced cell migration and cancer metastasis. In addition, FA is essential for preserving vascular integrity and loss of FAs leads to hemorrhages and is frequently observed in many vascular diseases such as intracranial aneurysms. As such, focal adhesions become an attractive therapeutic target for treating cancer or vascular diseases, two leading causes of death worldwide. FA is controlled by both its formation and turnover. In comparison to the large body of literature detailing FA formation, the mechanisms of FA turnover are poorly understood. Recently, autophagy emerges as a major mechanism to degrade FAs and stabilizing FAs by inhibiting autophagy has a beneficial effect on breast cancer metastasis, suggesting autophagy-mediated FA turnover is a promising drug target. Intriguingly, autophagy-mediated FA turnover is a selective process and the cargo receptors for recognizing FAs in the process are context-dependent, which ensures the degradation of specific cargo. Here, this paper mainly reviews the cargo recognition mechanisms of FA-phagy (selective autophagy-mediated FA turnover) and its disease relevance. We hope to provide some enlightenment for further study on FA-phagy and precise therapeutic strategies for related diseases associated with aberrant FA functions.